2000
DOI: 10.3923/jbs.2001.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of S1 Maize (Zea mays L.) Families at Seedling Stage under Drought Conditions

Abstract: Highly significant differences were found among S 1 maize families and treatments for all indicated traits except dry root weight which was non-significant among treatments. Treatments×S 1 families interaction was found significant for fresh shoot weight, dry shoot weight and fresh shoot length. The values of coefficient of variation for fresh shoot weight was found to higher than fresh root weight, dry root weight and dry shoot weight. Broad-sense heritability estimates were ranging between 54.27-83.99 percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…Higher shoot length suggests that higher crop biomass may be produced due to more water content, and an inbred line with a higher shoot length may be selected for fodder breeding as well as for quantitative traits. Similar results have been reported by Mehdi et al (2001). Several crosses in this trial led to substantial genetic advance, particularly under drought conditions (Tables 1 and 2 Pandey et al (2000) reported that increasing moisture stress was the major cause of decreases in crop growth rate, leaf area, shoot dry matter, plant height and harvesting index.…”
Section: Discussionsupporting
confidence: 73%
“…Higher shoot length suggests that higher crop biomass may be produced due to more water content, and an inbred line with a higher shoot length may be selected for fodder breeding as well as for quantitative traits. Similar results have been reported by Mehdi et al (2001). Several crosses in this trial led to substantial genetic advance, particularly under drought conditions (Tables 1 and 2 Pandey et al (2000) reported that increasing moisture stress was the major cause of decreases in crop growth rate, leaf area, shoot dry matter, plant height and harvesting index.…”
Section: Discussionsupporting
confidence: 73%
“…The present study confirmed this inspiration, for instance, the inbred line KUBA/GUDAC1� has 62 ears and provided a grain yield of 4.3 t ha -1 , whereas an inbreed line A7033 has 50 ears but offered 8.3 t ha -1 (Table 1). This result also agreed with the investigation of Mehdi et al (2001) and Taimur et al (2011) attained a smaller amount of coefficient of variation for several traits in maize and conferring to Singh and Chaudhry (1997), 10% or less CV are acceptable for selection of traits in improving the program for the population. Days to 50% pollen shedding for maize hybrids ranged from 62 to 76 (Table 1).…”
Section: Resultssupporting
confidence: 89%
“…Root dry weight has the potential to be an important trait for selection against water stress (Mehdi et al 2001). This study also confirmed the association between Tolerance and RDW (Table 3).…”
Section: Discussionsupporting
confidence: 82%